(untitled) (Universitas Scientiarum, 2004)
The formation possibility of the most widespread carbon compounds had been showed on the base of detonation nanodiamonds thermodynamic data. These reactions may play a key role in the life origin and in the atmosphere formation of the Solar system giant planets.